Planowanie finansowe warunkiem wzrostu efektywności funkcjonowania przedsiębiorstwa - Brycz, Bogumiła (Financial Planning as An Essential Condition of the Increase in An Enterprise Performance Efficiency, 2005)
The aim of this article is to show the importance of financial planning as an essential condition of the increase in an enterprise performance efficiency as well as to discuss financial planning methods and their practical applications. Consequently, the author starts with the definition of planning, concentrating first of all, on the differences between planning and forecasting and on the role played by financial planning in enterprise management. Next, the author discusses the methods of creating pro forma financial reports as they are the basic financial planning instrument. Finally, the author points out the importance of taking into account the risk of not achieving the desired results
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1060, s. 19-29